Clinical indicators of blood gas disturbances, elevated L-lactate concentration and other abnormal blood parameters in newborn beef calves. (January 2017) - Homerosky, E.R.; Caulkett, N.A.; Timsit, E.; Pajor, E.A.; Kastelic, J.P.; Windeyer, M.C.
Highlights: Incomplete tongue withdrawal and weak suckle reflex were associated with decreased blood pH and increased blood L-lactate. Calves of primiparous dams or assisted calving were more likely to have decreased blood pH and increased blood L-lactate. Lactate meters can be used to identify acidemic calves in a field setting, as blood L-lactate was highly correlated with pH. Abstract: Blood gas disturbances, commonly resulting from dystocia, are associated with failed transfer of passive immunity, morbidity and mortality in newborn calves. Modified APGAR scores intended to identify compromised calves are not widely adopted due to lack of practicality and inconsistent associations with blood parameters. The objective of this study was to determine clinical indicators of acidemia in newborn beef calves. Blood parameters at 10 min and 24 h after birth were compared to at-birth clinical examination parameters and calving characteristics in 77 commercial beef calves. There were no associations between heart rate or respiratory rate and blood pH or blood L-lactate concentration (LAC; r < 0.25); however, LAC was highly correlated with blood pH ( r, −0.86). Abnormal mucous membrane color (red, white or blue) was associated with increased LAC ( P = 0.002) but not decreased blood pH ( P = 0.07). Abnormal results for tests of muscle tonicity and reflexes, namely inability to completely withdraw the tongue when pinched and a weak suckle reflex, were associated with decreased blood pH and increased LAC ( P < 0.05). Calves born to primiparous dams or from an assisted calving also had decreased blood pH and increased LAC ( P < 0.05). Differences in blood pH between at-birth categories resolved for all parameters by 24 h after birth, except for tongue withdrawal ( P = 0.04). In conclusion, traditional APGAR parameters, heart rate, respiratory rate and mucous membrane color were not useful for the identification of acidemic calves; however, tongue withdrawal, calving ease, and parity should be included in such an assessment. Utilizing hand-held LAC meters may be a practical method to quickly identify compromised calves with acidemia in a field setting.